If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -1(7x + 2) = 2x + -15 Reorder the terms: 8x + -1(2 + 7x) = 2x + -15 8x + (2 * -1 + 7x * -1) = 2x + -15 8x + (-2 + -7x) = 2x + -15 Reorder the terms: -2 + 8x + -7x = 2x + -15 Combine like terms: 8x + -7x = 1x -2 + 1x = 2x + -15 Reorder the terms: -2 + 1x = -15 + 2x Solving -2 + 1x = -15 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -2 + 1x + -2x = -15 + 2x + -2x Combine like terms: 1x + -2x = -1x -2 + -1x = -15 + 2x + -2x Combine like terms: 2x + -2x = 0 -2 + -1x = -15 + 0 -2 + -1x = -15 Add '2' to each side of the equation. -2 + 2 + -1x = -15 + 2 Combine like terms: -2 + 2 = 0 0 + -1x = -15 + 2 -1x = -15 + 2 Combine like terms: -15 + 2 = -13 -1x = -13 Divide each side by '-1'. x = 13 Simplifying x = 13
| u^2-9u+20/3u^2+6u-105 | | B+0.8=0.72 | | 7x-(3x+3)=21 | | 0.8a=0.72 | | -50+10= | | 3(n)=48 | | 2(2x-1)+2(x+3)= | | 1x/2+1/4x=16 | | x-7.6=3.4 | | n-3=41 | | 2(2x-1)+2(x+2)= | | 3(n)=39 | | x^(3/2)-25x^(-1/2) | | 25(3x-(1/5)) | | 6(7-k)=84 | | 133+n=532 | | 3(4/2+3) | | 16n=-12 | | x+1/3x=72 | | -22.1/3.4 | | -24=c+9 | | p+30=19 | | 2/5x-5=11 | | 7(4c-1)-2=26c+7 | | -5m+8m=2m-7 | | n-6=44 | | -16=j-2 | | 116+n=443 | | 7x-5+(-3x)=-19+2 | | 1-6y= | | 17+d=-5 | | 4(x+1.54)=3x |